Social Solidarity in the Tradition of Mutual Cooperation: Indonesia Cultural Heritage - Sumitro, Sumitro; Agung Firmansyah; Micha Fiedlschuster; Wafa Affaghrou; Johnas Amon Buhori (Tinta Emas Publisher, 2024)
The tradition of mutual cooperation is an integral part of Indonesian culture that has developed over the centuries and plays an important role in building social solidarity in various communities. This research aims to explore the essence of mutual cooperation as Indonesia's cultural heritage and its relevance in contemporary social life. This study discusses the history and evolution of mutual cooperation in Indonesia, its implementation in people's lives, and its role in overcoming social conflicts and disasters. In addition, the study also identifies the challenges faced in preserving this tradition and revitalization efforts to strengthen social solidarity. The results of the study show that although the challenges of modernization and individualism threaten the sustainability of mutual cooperation, these values of togetherness are still relevant as a foundation for the development of an inclusive and cohesive society in Indonesia.